Evaluation of chitosan microparticles containing curcumin and crosslinked with sodium tripolyphosphate produced by spray drying - Alexandre Luis Parize; Hellen Karine Stulzer; Mauro César Marghetti Laranjeira; Inês Maria da Costa Brighente; Tereza Cristina Rozone de Souza (Química Nova, 2012)
The aim of this study was to encapsulate curcumin into chitosan, using sodium tripolyphosphate (TPP) as an ionic crosslinker by the spray drying method. The influence of TPP on the properties of the final product, such as solubility, morphology, loading efficiency, thermal behavior, swelling degree and release profiles, was evaluated. The microparticles had a spherical morphology (0.5-20 µm) with no apparent porosity or cracks. Results indicated the formation of a polymeric network, which ensures effective protection for curcumin. Controlled-release studies were carried out at pH 1.2 and 6.8, to observe the influence of pH on curcumin release while the mechanism was analyzed using the Korsmeyer-Peppas equation.